How can graph of f=-(x-1)^2+6 be obtained from y=x^2?  TOPIC_SOLVED

Quadratic equations and inequalities, variation equations, function notation, systems of equations, etc.

How can graph of f=-(x-1)^2+6 be obtained from y=x^2?

Postby cassiemike2000 on Sun May 10, 2009 12:29 am

I am taking an online finite math class and I am not getting this stuff.

How can the graph of f(x)= -(x-1)^2 +6 be obtained from the graph of y=x^2?

I don't understand how to do this and the book is no help.

Can someone please explain this to me and is there any other substition books that I can get that will help explain this stuff?

Thanks,
Cassie
cassiemike2000
 
Posts: 1
Joined: Sun May 10, 2009 12:26 am

Sponsor

Sponsor
 

  TOPIC_SOLVED

Postby stapel_eliz on Sun May 10, 2009 10:53 am

cassiemike2000 wrote:Can someone please explain this to me...?

To learn how to do function transformations and translations, try here. :wink:

Then note that, for g(x) = x2, the function f(x) = -(x - 1)2 + 6 is -g(x - 1) + 6....

:D
User avatar
stapel_eliz
 
Posts: 1705
Joined: Mon Dec 08, 2008 4:22 pm


Return to Intermediate Algebra

cron